2018
DOI: 10.1002/art.40514
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of Murine Osteoarthritis by Cartilage‐Specific Deletion of IκBζ

Abstract: These findings demonstrate a critical role for IκBζ in OA pathogenesis. Inhibition of IκBζ function might be an effective therapeutic approach for OA treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 44 publications
1
39
0
Order By: Relevance
“…Moreover, IκBζ was shown to form a complex with NF-kB [32]. Thus, IκBζ appears to be a novel player in the pathogenesis of inflammatory stimuli-induced osteoarthritis [31].…”
Section: Role Of Interleukin-1 (Il-1) and Nuclear Factor Kb (Nf-kb) Smentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, IκBζ was shown to form a complex with NF-kB [32]. Thus, IκBζ appears to be a novel player in the pathogenesis of inflammatory stimuli-induced osteoarthritis [31].…”
Section: Role Of Interleukin-1 (Il-1) and Nuclear Factor Kb (Nf-kb) Smentioning
confidence: 99%
“…Nuclear factor of κ light polypeptide gene enhancer in B cells inhibitor zeta (IκBζ) was initially proposed to function as an inhibitory molecule for NF-κB; however, it has been shown that IκBζ also mediates inflammatory signals downstream of IL-1 and TNFα [29,30]. IL-1β upregulated IκBζ expression in chondrocytes, and IκBζ expression was found to be increased in cartilage tissues of patients with osteoarthritis [31]. Cartilage-specific IκBζ-conditional knockout (KO) mice exhibited suppressed development of osteoarthritis.…”
Section: Role Of Interleukin-1 (Il-1) and Nuclear Factor Kb (Nf-kb) Smentioning
confidence: 99%
“…Moreover, IκBζ was shown to form a complex with NF-ĸB [26]. Thus, IκBζ appears to be a novel player in the pathogenesis of inflammatory stimuli-induced osteoarthritis [25].…”
Section: Role Of Nf-ĸb Signaling In Osteoarthritismentioning
confidence: 99%
“…Nuclear factor of κ light polypeptide gene enhancer in B cells inhibitor zeta (IκBζ) was initially proposed to function as an inhibitory molecule for NF-κB; however, it has been shown that IκBζ also mediates inflammatory signals as downstream of IL-1 and TNFα [23,24]. IL-1β upregulated IκBζ expression in chondrocytes, and IκBζ expression was found to be increased in cartilage tissues of patients with osteoarthritis [25]. Cartilage-specific IκBζ conditional-knockout (KO) mice exhibited suppressed development of osteoarthritis.…”
Section: Role Of Nf-ĸb Signaling In Osteoarthritismentioning
confidence: 99%
See 1 more Smart Citation